Using Web-based Intelligent Tutoring Systems in Teaching Physics Subjects at Undergraduate Level - Erdemir, Mustafa (Horizon Research Publishing Co., Ltd., 2019)
The aim of the study is to draw attention to the importance of using web-based intelligent tutoring systems (WBITS), which have emerged as a result of artificial neural networks and technological developments (communication technology), in the teaching of physics subjects. A WBITS is an intelligent tutoring system that exhibits behavior similar to that of a teacher in the traditional educational process (classroom education), offers a flexible teaching process, defined according to user preferences, and adaptable for a specific purpose. WBITSs make important contributions to distance education and classroom education processes, because they can be used online and offline. The importance of using WBITSs in teaching physics at undergraduate level was subsumed under five headings: i). Developments in technology and artificial neural networks and the interest of young people in technology have made it important to use WBITSs in undergraduate physics education. ii) The use of WBITSs has become important in following scientific developments in traditional (classroom) physics education and eliminating problems related to individual perception capacity and insufficient class hours. iii). Online (remote) access to physics subjects via WBITSs contributes to equality of opportunity in education. iv). More time can be devoted to practice and the discussion of deeper (advanced) subjects in the classroom when basic physics subjects are taught at undergraduate (university) level using WBITSs. v). Limitations in distance physics education can be reduced using WBITSs.
Keywords: 4. Education